Anisakis sp. dan Alergi yang Diakibatkannya - Robiatul Adawiyah; Esy Maryanti; Forman E.Siagian (Jurnal Ilmu Kedokteran, 2014)
Parasitic diseases were initially found in many endemic areas, but currently also found in non endemic areas.One is anisakiasis caused by Anisakis sp. Humans can be infected by this parasite by direct consumpt the organismand contact with the fish / products of food that containing this parasite.There are some points that can increase therisk of infection of this parasite, high movement of people from one area to another either temporary or permanent,the food processing especially in the case of the fish packing, the advance of transportation that enables the widespreadof marine products which contaminated and how to eat the fish which contaminated. Anisakis sp. Antigen derivedfrom the excretion-secretion products, somatic and cuticular of the parasite larvae. Good hygiene and understandingof the problem and potential risk will increase alertness and awareness of Anisakis sp.infections